Firm Characteristics and Sales Growth in Explaining Tax Aggressiveness in Property Sector - Jayanto, Wendy (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to examine the effect of Firm Size, Firm Risk, Capital Intensity and Inventory Intensity on Tax Aggressiveness with Sales Growth as a Moderation Construct in Property & Real Estate Sector Businesses Listed on the IDX during 2020-2023. The study design carried out in this study is a quantitative study. The population of this study is all businesses in the Property & Real Estate sector recorded on the IDX during 2020-2023, namely 81 entities. Based on the purposive technique, a sample of 16 entities was obtained. So the data carried out in this study is as many as 64 (16 X 4 Years) entity data. The data analysis techniques used were descriptive statistical analysis, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test and autocholinity test), hypothesis test (t test and determination coefficient) and moderated regression analysis. The results of this study are Firm Size has a negative effect and sig on Tax Aggressiveness, Firm Risk has a positive effect and sig on Tax Aggressiveness, Capital Intensity has no effect on Tax Aggressiveness, Inventory Intensity has a positive effect and sig on Tax Aggressiveness, Firm Size has a negative effect and sig on Tax Aggressiveness moderated by Sales Growth, Firm Risk has a positive effect and sig on Tax Aggressiveness moderated by Sales Growth